The Role of Financial Performance in Moderating Capital Structure and Macroeconomic Uncertainty on Stock Returns: Study on the Trade and Services Sector of the Indonesia Sharia Stock Index - Nurul Fitri; Sigid Eko Pramono (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2023)
This study aims to investigate the relationship between capital structure and macroeconomic uncertainty on stock returns moderated by financial performance in trade and service sector issuers in the context of the Islamic capital market. The Structural Equation Modeling (SEM) method was applied using IBM AMOS Version 22 software. A total of 27 issuers in the trade and services sector listed on the Indonesian Sharia Stock Index (ISSI) became the research sample, which was observed in the time span from 2017 to 2022. The results showed that capital structure has no significant effect on stock returns, while macroeconomic uncertainty has a significant effect on stock returns. In addition, financial performance has a positive effect on stock returns. However, financial performance does not moderate the effect of capital structure on stock returns, while moderating the effect of macroeconomic uncertainty on stock returns. These findings provide new insights in the understanding of the factors that affect stock returns with practical implications for investors and company management.